The high‐efficiency co‐design and the measurement verification of high‐bandwidth silicon photonic microring modulator. Issue 6 (9th June 2022) - Wu, Yue; He, Huimin; Cao, Rui; Liu, Fengman
Abstract: The microring modulator (MRM) is a small‐size and low‐power component, which is the potential for the next‐generation optical interconnection. By the theoretical analysis, increasing the electrical bandwidth, which is relevant to the cross section and the doping concentration of the doping region, is a better way to increase electro‐optical (EO) bandwidth. Therefore, a new doping profile of the PN depletion region with 4 doping concentration levels is introduced considering the electrical bandwidth. Based on the new doping profile, the MRM with the 160 μm length and the 0.33 and 0.2 μm coupling space are determined considering the trade‐off between the EO bandwidth, quality factor ( Q ), extinction ratio, area of MRM, and power consumption. Moreover, the MRM is characterised and is applied in a wavelength division multiplexing transmitter. By the measurement, the transmitter with the designed MRM could transmit PAM4 signal at 52 Gbps rate, which indicates the MRM could be potential for the 50 Gbps/ch optical interconnection.